PENGATURAN LARANGAN PENGGUNAAN FASILITAS NEGARA DALAM PELAKSANAAN KAMPANYE POLITIK PEMILIHAN UMUM - I Wayan Mahesa Juli Susanto; I Nyoman Suandika; Kadek Dedy Suryana (Yayasan Nusantara Hasana Berdikari, 2024)
Campaigning is a candidate's activity carried out to gain public sympathy by showing, offering and announcing a vision and mission aimed at occupying and leading a government. In carrying out political campaigns, there are rules and prohibitions for state and regional officials, namely the prohibition on using state facilities. It is difficult to separate the covert campaign to use state facilities from carrying out one's duties as an official or regional head. This issue certainly needs to receive serious attention, in order to create clean, honest and fair general elections. Therefore, the problem raised in this research is how to regulate the prohibition on the use of state facilities in campaign implementation based on election law regulations, and what are the legal consequences of using state facilities in campaign implementation based on election law regulations? This research uses normative legal research methods or library legal research methods, which are legal research methods carried out by examining library materials related to written legal norms (legislation) which aims to discover or obtain legal principles from positive law. written by the community. Based on the results of research that has been carried out, regulations prohibiting the use of state facilities in the implementation of political campaigns have been regulated in the provisions of Law Number 7 of 2017 concerning General Elections. The application of sanctions as a legal consequence of the use of state facilities in campaign implementation is based on general election law regulations, which consist of 2 (two) legal sanctions, namely administrative sanctions and criminal sanctions. It is necessary to make clearer and firmer regulations regarding all forms of fraud and violations in the general election and the public is expected to play an active role in participating in overcoming all kinds of fraud in the general election, one of which is violations in the use of state facilities in political campaigns as an effort to ensure that the general election can be held. proceed fairly.